Компаньон ее сиятельства: роман / Эванджелина Коллинз - Коллинз Эванджелина (Очарование, 2010)
Экземпляры: АБ (20180924) / Инвентарный номер: 53337 / Цена: 79.80 / Сис.шифр: 84(7Сое) / Авт.знак: К 60 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)